Structure and Written Expressions of the TOEFL: Linguistic and Non-Linguistic Constraints (Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
This study aimed at investigating the students’ linguistic and non-linguistic constraints in doing the Structure and Written Expression section of the TOEFL. This was a qualitative study in the form of a case study and was carried out in two universities in Magelang, Central Java, Indonesia. The data comprised document analysis on 42 students’ answer sheets on TOEFL and interviews with four students. The data were analyzed using the difficulty index (IF) formula proposed by Brown (2004) and the interactive model developed by Miles and Huberman (1994) for quantitative and qualitative data, respectively. The findings revealed that the students encountered three linguistic constraints in terms of grammatical items as caused by both intralingual and interlingual interference: active-passive verbs, double comparatives, and pronoun-noun agreement. Besides, non-linguistic factors such as unpleasant past learning experiences and limited exposure to the L2 worsened their performance on the test.